Asymptomatic complete distal abdominal aortic occlusion with initial presentation of ruptured intracranial aneurysm - Chandran Nadarajan; Amirah Abdul Wahid; Chiak Yot Ng; Juhara Haron; Jeremiah Sunderaj Peter; Mohd Fariq Mohd Yusof (Elsevier Inc., 2021)
Aortoilliac occlusive disease is occlusive atherosclerosis disease involving the distal aorta and bifurcation of iliac arteries and it is a subtype of peripheral arterial disease. Total occlusion of the abdominal aorta is a rare occurrence with an incidence of 3% -8.5% among the aortoiliac occlusive disease patients. We present a case of a 53 years old patient with a background history of hypertension and ex intravenous drug abuser with negative retroviral screening status, with no previous complaints who was brought to the Emergency Department with sudden onset of altered sensorium and 1 episode of seizure. Computed tomography angiogram of the brain showed a ruptured anterior communicating artery aneurysm. Diagnostic conventional angiogram of the brain was planned; however, difficulty was encountered during bilateral femoral artery cannulation with the abrupt termination of bilateral common iliac arteries. Computed tomography angiogram of the abdomen showed incidental finding of total occlusion of the abdominal aorta. As a conclusion, total occlusion of abdominal aorta secondary to aortoiliac occlusive disease with an associated intracranial aneurysm is never reported in the literature to date. This case highlights the possibility of association in between these two conditions which may benefit from further research.